Atomically Precise Gold Nanoclusters Accelerate Hydrogen Evolution over MoS2 Nanosheets: The Dual Interfacial Effect. Issue 43 (24th July 2017) - Zhao, Shuo; Jin, Renxi; Song, Yongbo; Zhang, Hui; House, Stephen D.; Yang, Judith C.; Jin, Rongchao
Abstract: Hydrogen generation via electrocatalytic water splitting holds great promise for future energy revolution. It is desirable to design abundant and efficient catalysts and achieve mechanistic understanding of hydrogen evolution reaction (HER). Here, this paper reports a strategy for improving HER performance of molybdenum disulfide (MoS2 ) via introducing gold nanoclusters as a cocatalyst. Compared to plain MoS2 nanosheets, the Au25 (SR)18 /MoS2 nanocomposite exhibits enhanced HER activity with a small onset potential of −0.20 V (vs reversible hydrogen electrode) and a higher current density of 59.3 mA cm −2 at the potential of −0.4 V. In addition to the interfacial interaction between nanoclusters and MoS2, the interface between the Au25 core and the surface ligands (thiolate vs selenolate) is also discovered to distinctly affect the catalytic performance. This work highlights the promise of metal nanoclusters in boosting the HER performance via tailoring the interfacial electronic interactions between gold nanoclusters and MoS2 nanosheets, as well as the interface between metal core and surface ligands. Abstract : A novel strategy of enhancing the hydrogen evolution reaction (HER) performance of MoS2 via gold nanocluster functionalization is presented. Owing to the molecular purity along with known structure of nanoclusters, atomic‐level understanding is achieved, and attributes the HER enhancement to the unique electronic interactions between nanoclusters and MoS2 nanosheets, in particular the interfacial effect.